2011 3rd Workshop on Hyperspectral Image and Signal Processing: Evolution in Remote Sensing (WHISPERS) 2011
DOI: 10.1109/whispers.2011.6080862
|View full text |Cite
|
Sign up to set email alerts
|

Compression-based unsupervised clustering of spectral signatures

Abstract: This paper proposes to use compression-based similarity measures to cluster spectral signatures on the basis of their similarities. Such universal distances estimate the shared information between two objects by comparing their compression factors, which can be obtained by any standard compressor. Experiments on rocks categorization show that these methods may outperform traditional choices for spectral distances based on vector processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…We consider a dataset used in [2] to test a proposed compression-based similarity measure for time series, the Normalized Compression Distance (NCD). The authors in [2] compared NCD with Euclidean Distance, Spectral Angle, Spectral Correlation, and Spectral Information Divergence on a set of 41 spectra from three different classes of rock, and showed that their proposed distance measure gives the best clustering results in this domain.…”
Section: Rock Categorizationmentioning
confidence: 99%
See 3 more Smart Citations
“…We consider a dataset used in [2] to test a proposed compression-based similarity measure for time series, the Normalized Compression Distance (NCD). The authors in [2] compared NCD with Euclidean Distance, Spectral Angle, Spectral Correlation, and Spectral Information Divergence on a set of 41 spectra from three different classes of rock, and showed that their proposed distance measure gives the best clustering results in this domain.…”
Section: Rock Categorizationmentioning
confidence: 99%
“…The authors in [2] compared NCD with Euclidean Distance, Spectral Angle, Spectral Correlation, and Spectral Information Divergence on a set of 41 spectra from three different classes of rock, and showed that their proposed distance measure gives the best clustering results in this domain.…”
Section: Rock Categorizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Such distance can be applied to diverse data types [11], and one of its main advantages is its parameter-free approach, as the NCD depends only on the compressor adopted, with performance comparisons for general compression algorithms showing this dependance to be loose [12]. The NCD and its variants have been applied to spectral signatures collected from hyperspectral sensors [13,14], SAR images [15], multispectral data and satellite image time series [8,16].…”
Section: Preliminariesmentioning
confidence: 99%